Facility Analysis on Customer Satisfaction at Ksatria Kopi - Heykal, Muhammad; Rahman, Faishal; Wardhani, Hilda Sari (International Journal on Advanced Science, Education, and Religion, 2025)
The growing number of coffee shops in urban areas has intensified competition, including for Ksatria Kopi. Adequate facilities have become one of the key factors influencing customer comfort and satisfaction. This study aims to analyze the effect of facilities on customer satisfaction at Ksatria Kopi. This research employed a quantitative method with a survey approach using an online questionnaire distributed to 75 respondents. The respondents were selected using a non-probability accidental sampling technique based on gender, education, and age criteria. Data were analyzed using Microsoft Excel and IBM SPSS Statistics 25 through validity and reliability tests, classical assumption tests, simple linear regression analysis, and hypothesis testing. The results indicate that facilities have a positive and significant effect on customer satisfaction, as evidenced by the regression equation Y = 7.151 + 0.661X and an R² value of 0.810. This means that 81% of the variation in customer satisfaction can be explained by facilities, while the remaining 19% is influenced by other factors outside this study. The conclusion of this research is that the better the facilities provided, the higher the level of customer satisfaction. The originality of this study lies in its specific focus on a single object, Ksatria Kopi, which has not been extensively examined quantitatively in the context of the coffee shop industry in this region. These findings provide practical implications for Ksatria Kopi’s management to improve facility quality in order to retain and attract customers.